No Last Words - Chong, Su Li (International Association of Computer Science and Information Technology (IACSIT), 2009)
As social science researchers, we are uniquely and even fortunately supported by the vastness of our ‘social science lab’. Our community is that fertile ground from which we draw behaviors, voices, statistics and ideas. From these, we derive hypotheses, predictions, and implications. When so much of our understanding of human behavior hinges on these observed and inferred findings, it is crucial for researchers to be aware of the potential of their data sets. This paper therefore, puts forth the concept of infiniteness in research findings. To do that, I borrow notions from dialogism and apply them into my own research on literacy. Such meta-analysis becomes useful for researchers to re-open the loop that often encircles and by that, delimits knowledge creation.